Radiopharmaceutical Encapsulated Liposomes as a Novel Radiotracer Im - aging and Drug Delivery Protocol - Alkandari, Anfal M.; Alsayed, Yasser M.; El-hanbaly, Atallah M. (Current Radiopharmaceuticals, 2023)
Nuclear medicine specialty involves the administration of unsealed radioactive substances to patients to allow specific diagnostics and treatments using radiopharmaceuticals, radiotracers, and materials. Developing a radiopharmaceutical must involve considering and addressing some limitations such as its retention by unintended organs, which can influence patient and worker safety, imaging findings, and diagnostic and therapeutic accuracy. This paper presents data on the changing biodistribution, localization, stability, and accuracy patterns of radiopharmaceuticals by liposome encapsulation. Methods: Data are presented for 5 male New Zealand white rabbits. They were injected intravenously with the 99mTc-liposomes encapsulated MIBI through a marginal ear vein, and whole-body images were acquired using a dual-head gamma camera. Cationic PEGylated liposomes were prepared using the conventional thin-film-hydration method. The liposomes were tested for particle size, zeta potential, high-performance-liquid-chromatography (HPLC), and toxicity. Results: The liver activity was slightly greater than or equivalent to heart uptake, using 99mTcsestamibi, MIBI, without liposome as a reference. The absorbed doses in myocardium cells after injecting rabbits with 99mTc-MIBI labeled with free positive lower pH liposomes was greater than in the liver, whereas 99mTc labeled with encapsulated MIBI within positive liposomes showed a significantly higher heart-to-liver ratio. The heart-to-spleen activity uptake ratio in 99mTc-MIBI was higher than or equal to one but increased in 99mTc labeled with MIBI and free positive liposomes. Injecting rabbits with 99mTc labeled with encapsulated MIBI raised myocardium uptake to 2-4 times more than the spleen. Heart-to-bowel activity began to rise with 99m Tc-labeld-MIBI and liposomes. Conclusion: This study provides findings in radiopharmaceutical biodistribution using liposomal agents. Adding free liposomes using a pH gradient technique enhanced the uptake and localization of the radiotracer. However, tracer encapsulation during the formation of the liposomes showed even better specificity.
Keywords: Myocardial-imaging